THE IMPORTANCE OF ISOSTRETCHING FOR PREVENTING INJURIES AND PAIN IN THE LUMBAR REGION IN WOMEN (Fiep Bulletin - online, 2012)
Being Isostretching a gymnastic therapeutically composed of exercises that simultaneously allow isometric stretching and strengthening of some muscular groupings, acting in the prevention and the treatment of the bony-muscular alterations, with this study we aimed at making a comparison among experiments already carried through with this method as base for prevention and/or treatment of backaches. In order to base it, five researches were used, from which results have been analyzed and discussed. As a conclusion, it was verified that the method was beneficial in all of them.
Keywords: backache; case study